CSR and its impact on a company's corporate financial performance : do firms that engage in CSR activities have better financial performance? A European case study - Fernandes, Maria Margarida Mesquita (2022)
The present thesis investigates the relationship between a company’s corporate social responsibility (CSR) performance and its financial performance (FP), in a European context. Three different methods were used in this study: first, an OLS and fixed-effects approaches were employed to examine this link during a 10-year period (2010-2020) of firms listed on the STOXX Europe 600 index (2,681 firm-year observations). The explanatory variable (CSR) is assessed through firm’s total Environmental, Social and Governance (ESG) scores and the individual scores of the three ESG components, while the explained variables (FP) are measured by the Return on Assets (ROA) and Tobin’s Q. The results show that, when we use ESG score as the explanatory variable, there is a significant positive relationship with firm value (Tobin’s Q), both at 1-year and 2-year lag. However, contrary to prior research on sustainability performance, no evidence is found that CSR performance has an impact on a company’s ROA. Concluding the analysis with a 2SLS regression test, the outcomes showed a stronger positive link for the dependent variable Tobin's Q, and did not show any changes in the relationship with ROA. When we do the same investigation for the individual ESG components, we find that Governance performance has the strongest impact on FP. These findings partially support the view that CSR creates value and is a key contribute to a firm’s FP.